Gending Meong-Meong Sebagai Media Penanaman Nilai-Nilai Kejujuran Pada Anak Usia Dini Di PAUD Dewi Srikandi Lestari - Sudiani, Ni Nyoman; Saklit, I Wayan; Utami Dewi, Dian Syanita; Meysa, Jesika (Jayapangus Press, 2025)
Honesty is an important behavior for everyone. Until now there is still news about corruptors, meaning there are still dishonest people. Honesty cannot be taught when they are adults. Honesty must be instilled in children from an early childhood. This study aims to re-explore the benefits of gending rare because Hindus, especially those domiciled in Jakarta and its surroundings, are less familiar with it, even though gending rare is effective as an educational medium for children. Gending Rare is known to be full of educational values. This study examines Gending Meong-meong as a medium for instilling honesty values ​​in early childhood. This study is a qualitative study that explores and describes the opinions of teachers at Dewi Srikandi Lestari Bekasi PAUD regarding gending Meong-meong. Data collection through interviews with Dewi Srikandi Lestari PAUD teachers as teachers and parents, and observations on gending Meong-meong. The results of the study of honesty values ​​in Gending Meong-meong are satya wacana, satya laksana, satya mitra and satya hredaya; and the time to sing Gending Meong-meong to early childhood to instill honesty values ​​is when children are relaxing, playing, studying and going to bed. At that time is the right time to sing and instill honesty to early childhood. The contribution of this research to the world of education is that there is Gending Meong-meong which is effective as a medium for instilling honesty values ​​for early childhood. Therefore, this Gending must be preserved and required as an educational medium by teachers at school and parents.